Управління економічною безпекою сільськогосподарських підприємств - Стадник, Вікторія Павлівна (НУБіП України, 2016)
Дисертація на здобуття наукового ступеня кандидата економічних наук за спеціальністю 08.00.04 – економіка та управління підприємствами (за видами економічної діяльності). – Національний університет біоресурсів і природокористування України, Київ, 2016. У дисертаційній роботі поглиблено теоретичні аспекти управління економічною безпекою з метою розширення його наукової сутності та структури. Розкрито й уточнено поняття «управління економічною безпекою підприємств», яке на відміну від існуючих трактувань розкриває управління економічною безпекою підприємств із позиції поєднання сукупності дій, що базуються на захищеності важливих інтересів підприємства від зовнішніх та внутрішніх загроз, використанні можливостей досягнення цілей загальносистемного спрямування та реалізації власних економічних інтересів в умовах невизначеності та господарських ризиків. Запропоновано методичний підхід до оцінки рівня економічної безпеки сільськогосподарських підприємств на основі визначення інтегрального показника, що включає багатокритеріальний вимір функціональних складових системи управління виробничою діяльністю господарюючих суб’єктів. Систематизовано ключові чинники економічного розвитку сільськогосподарських підприємств, що є визначальними при оцінці економічної безпеки суб’єктів господарювання. Визначено стратегічні напрями стабілізації та розвитку сільськогосподарських підприємств, як факторів управлінського впливу. Розроблено пропозиції, щодо удосконалення управління економічною безпекою сільськогосподарських підприємств на засадах екологізації виробництва сільськогосподарської продукції. Удосконалено систему управління економічною безпекою сільськогосподарського підприємства.
Thesis for the candidate of economic sciences in specialty 08.00.04 – Economics and Management of the Enterprises (according to the types of economic activity). National University of Life and Environmental Sciences of Ukraine. – Kyiv, 2016. The thesis deals with such an urgent scientific task as the theoretical and methodical approaches and practical recommendations according economical security management of agricultural enterprises. It is summarized the totality of “economic security” and “economic security management” definitions what allows to understand them deeper. Taking into account proposed definitions and proposals and on the base of systematic approach it is formed the definition of economic security management as the process of working out and realization of measures which based on vitally important enterprise interests security from internal and external threats, formed opportunities of goals achievement using, own economic interests realization, competitive advantages and encourage enterprise stable position securing in conditions of instability and economic risks. It is proved in this thesis that in modern conditions of scientific and technical progress for effective economic security management of agricultural enterprises it the development is needed. The classification of economic security threats is systematized and it consists of situation assessment and assessment of negative moments and on these base well-founded recommendations for concrete measures using as to its impact liquidation. It is analyzed the tendencies of development and operation features of agricultural enterprises. Made analysis of development of agricultural enterprises operation shows the tendency of their quantity declining. It is defined that in the dynamics in structure plant cultivation producing prevails. According to the investigation results agricultural enterprises take more part in plant cultivation producing than in animal breeding. It is given the assessment of enterprise internal environment and defined positive and negative factors impact on the level of economic security management. It is extended investigations of economic security level assessment of agricultural enterprises. It is analyzed operation of enterprises of Nizhynskii, Prilutskii and Ichnyznskii districts of Chernigovskii region which are grouped by proposed security level according to elements of economic security integrated indicator. It is defined that crisis result is 0,15, min (0,15 – 0,30), low (0,3 – 0,45), medium (0,45 – 0,75), more than 0,75 – high security level. Made correlation analysis allowed defining relation between integrated index of economic security of agricultural enterprise operation, particularly its elements and indicator of enterprise operation effectiveness which allowed making such conclusions: the highest impact on indicator of effective operation of agricultural enterprise financing makes, besides personnel and information elements play an important role, especially concerning innovative technological information and information about changes of the enterprises markets conjuncture. It is caused by the fact that for the agricultural enterprises land is the main producing factor and ecologic state has an impact on the results of agricultural business. According to the SWOT-analysis results it is defined that in producing modern conditions it is necessary to use corporative strategies which encourage ensuring effective management of enterprise economic security in the dynamic environment. It is proved the ways of improvement of effectiveness of agricultural enterprises economic security management. On the base of the systematic approach it is built a technology of agricultural enterprises forming development corporative strategies technology. Such technology provides choosing of strategic direction of enterprises development; analysis of influence factors of internal and external environment which provides systematic using; making corporative strategies of agricultural enterprises development and its effectiveness assessment. It is grounded that the improvement of agricultural enterprises economic security management depends on high intellectual level of labor that is way it is necessary to develop personnel activity in the sphere of innovation development. Achievement of effective management of economic security depends on ability of management structures to ensure the interest of labor in goals achievement. In the study it is proposed for solutions grounding regarding improvement of agricultural enterprises economic security level in which it is put the necessity of ecologic products producing, usefulness of agrarian lands for producing ecological products according to the main agro-chemical indicators based on the principle of administrative districts and showed optimized variants of development of ecological products producing by the prognosis method. It is defined that the technology of organic farming got an expansion in the developed countries. Ukrainian agricultural enterprises have to use foreign experience what encourage development of agricultural products markets in Ukraine. Scientifically proved that ecological producing encourages the improvement of competitiveness advantages, gains of new segments and improvement of enterprises competitiveness. During the investigation it is grounded the system of agricultural enterprises security management system which provides the complex of managing, economic, organizing, legislative and controlling and motivation ways of harmonization enterprise interests with the interests of external environment subjects accounting features of enterprise operation. Economic security management system must be structured according to the organizational elements of specialized agencies, services, tools, methods, measures that protect the vital interests of the enterprises from internal and external threats in order to maintain economic stability and profitability management.
Keywords: економічна безпека; загроза; функціональні складові; чинники; управління економічною безпекою; інтегральний показник; система управління; сільськогосподарські підприємства; economic security; threat; functional components; factors; agricultural enterprises